Political participation of women in elections: A brief analysis in political life / Zaherawati Zakaria...[et al.] - Zakaria, Zaherawati; Noordin, Nazni; Mohamed Sawal, Mohd Zool Hilmie (2010)
The study of political participation has traditionally been considered as central to the analysis of political processes and, especially, of democratic political systems. Recent decades have witnessed growing demands for the empowerment of women and in political participation. Feminist theorists suggest that the presence of women leaders facilitates the articulation of different perspectives on political issues, where elected representatives are not just ‘standing as’ women but also ‘acting for’ women as a group. There is no consensus around which is the most adequate level of citizen participation (men or women) in the government of the polity for a good functioning of democracy. Women as one of the key values of democratic polities, so that all major social cleavages have a voice in the policymaking process, whether the politically relevant groups are defined by gender, ethnicity, region, socioeconomic status, age, or education. Thus, this paper tries to explain that those women who can mobilize themselves are more likely participate in political activities such as involve in campaigning week, demonstration, voting and even as candidate in elections .